La accesibilidad tecnológica en el ejercicio de derechos sucesorios: Análisis de su implementación y viabilidad del testamento electrónico - Naranjo Romero, Andrea Fernanda (2025)
Information and Communication Technologies (ICTs) have gained increasing relevance worldwide, particularly following the COVID-19 pandemic, which accelerated the adoption of technological means in various fields, including the legal field. In this context, this research addresses technological accessibility in the exercise of inheritance rights, with special emphasis on testamentary acts, defining technological accessibility as the provision of digital resources to individuals. The present study aimed to analyze the characteristics and legal foundations of electronic wills within the context of inheritance law, through an exhaustive examination of doctrine, comparative regulations, and a critical analysis of current legislation. This study aimed to assess the feasibility and relevance of implementing electronic wills in Ecuadorian law. To this end, a qualitative methodology was employed, involving interviews with notaries and surveys conducted among legal professionals and citizens of the Riobamba canton, Chimborazo province, to identify perceptions and acceptance of electronic wills. The results revealed a significant gap in Ecuadorian legislation, which lacks specific provisions for the validity of electronic wills, thereby limiting access to this type of technological tool in inheritance law. It is concluded that the implementation of electronic wills in Ecuador would represent a significant advance in terms of accessibility and modernization of the legal system. The coexistence of electronic and traditional wills would provide greater flexibility for citizens, facilitating the exercise of inheritance rights for people with physical and geographical barriers that prevent them from physically visiting a notary.